The birth of the New Testament - Moule, C. F. D. (Charles Francis Digby), 1908-2007 (Black's New Testament commentaries., 1981)
C.F.D. Moule shows how the earliest Christian writing developed as a response to the daily demands of Christian life in societies indifferent or even hostile to Christianity, and how the selection of certain writings to constitute the basis of Christian belief was a response to specific needs.